Radiological outcomes of bimalleolar fractures: are timing of surgery and type of implant important? - Sara Catarina Oliveira Guedes (2020)
Background: The goal of open reduction and internal fixation (ORIF) of bimalleolar ankle fractures is to reconstitute ankle anatomy. The most commonly used radiological parameters to assess adequacy of reduction are tibiofibular clear space (TFCS), tibiofibular overlap (TFO), talocrural angle (TCA) and medial clear space (MCS). There is little research about the radiological outcomes of surgery in bimalleolar fractures. We aimed at assessing the adequacy of ORIF and the factors involved in anatomical restoration, postoperatively and at follow-up. Methods: TCA, MCS, TFO and TFCS were measured in preoperative, postoperative and follow-up radiographs of 107 bimalleolar ankle fractures. Preoperative radiographs were categorized according to Danis-Weber classification. For all included cases, basic demographic data, dates of radiographs and surgery, and type of fixation used were acquired. Variables associated with postoperative and follow-up total anatomical reconstitution, normalization of each radiological parameter, and improvement in the number of normalized radiological parameters were identified through univariable Cox regression analyses. Results: In our sample, 23.8% of the ankle fractures in postoperative radiographs and 28% in follow-up radiographs achieved a complete anatomical restoration. Waiting days until surgery (hazard ratio [HR] = 0.8, 95% confidence interval [CI] = 0.6-0.9, P = .012) and type C fractures (HR = 0.1, 95% CI = 0.02-0.7, P = .021) associated with lower chances of total anatomical reconstitution. Waiting days until surgery (HR = 0.9, 95% CI = 0.9-1.0, P = .045) and the use of reconstruction plates (HR = 0.1, 95% CI = 0.03-0.7, P = .014) and one third tubular plates (HR = 0.2, 95% CI = 0.03-0.8, P = .026) decreased the chances of improving the number of normalized radiological parameters. Conclusion: Our results suggest that ORIF should be accomplished as soon as possible using appropriate fixation materials, in order to achieve a better anatomical restoration.